In-School Work Experience, Parental Allowances, and Wages - Christian Dustmann; John Micklewright; Arthur van Soest (Institute for the Study of Labor (IZA), 2004)
In many industrialised countries, teenagers have a significant spending power, and they are important customers for specialised industries. The income of teenagers still in full time education comes from two major sources: parental pocket money, and earnings from part time jobs. Little is known about the way these sources interact, and how they depend on parental, school and family characteristics. In this paper, we analyse labour supply of 16 year old British teenagers together with the cash transfers made to them by their parents. We develop a theoretical model, which serves as a basis for the empirical specification in which labour supply and transfers are jointly determined. We estimate this model using unique data on labour supply of teenagers, the wages they receive, and transfers made to them by their parents. We show how these two processes depend on each other, and how transfers and labour supply react to changes in wages.
Keywords: J22; C7; C35; 330; intra-household transfers; teenager labour supply; Jugendliche; Arbeitsangebot; Privater Transfer; Lohn; Schätzung; Jugendliche Arbeitskräfte; Grossbritannien